#頭條創作挑戰賽#
a≠±1、0
解法①:依題意a≠0,a2≠0
∴1/(1-1/a)2+1/(1+1/a)2=6
令1-1/a=x,1+1/a=y
∴1/x2+1/y2=6
∴x2+y2=6x2y2…①
x+y=2…②
由②:x2+y2=(x+y)2-2xy=4-2xy…③代入①
4-2xy=6x2y2
∴3(xy)+xy-2=0
∴(3xy-2)(xy+1)=0
∴xy=2/3或xy=-1
當xy=2/3時,(1-1/a)(1+1/a)=2/3
∴1-1/a2=2/3,a2=3,a=±√3
當xy=-1時,(1-1/a)(1+1/a)=-1
∴1-1/a2=-1,a2=1/2,a=±√2/2
∴原方程得解為:a1=√3,a2=-√3,a3=√2/2,a4=-√2/2
解法②:分析:[a/(a-1)+a/(a+1)]2
=[2a2/(a2-1)]2
2.a/(a-1).a/(a+1)=2a2/(a2-1)
∴原方程可變為
[a2/(a-1)2+2.a/(a-1).a/(a+1)+a2/(a+1)2]-2.a/(a-1).a/(a+1)-6=0
∴[a/(a-1)+a/(a+1)]2-2a2/(a2-1)-6=0
∴[2a2/(a2-1)]2-2a2/(a2-1)-6=0
令2a2/(a2-1)=x
∴x2-x-6=0
∴(x-3)(x+2)=0
∴x=3或x=-2
當x=3時,2a2/(a2-1)=3,a=±√3
當x=-2時,2a2/(a2-1)=-2,a=±√2/2
∴原方程得解為:a1=√3,a2=-√3,a3=√2/2,a4=-√2/2
解法③:分析:a/(a-1)+a/(a+1)
=(a2+a+a2-a)/(a2-1)=2a2/(a2-1)
a/(a-1).a/(a+1)=a2/(a2-1)
令a/(a-1)=x,a/(a+1)=y
∴x2+y2=6…①
x+y=2xy…②
由①:(x+y)2-2xy=6…③
將②代入③:(x+y)2-(x+y)-6=0
∴[(x+y)-3][(x+y)+2]=0
∴x+y=3或x+y=-2
當x+y=3時,xy=3/2
∴2a2/(a2-1)=3,∴2a2=3a2-3,∴a=±√3
當x+y=-2時,xy=-1
∴2a2/(a2-1)=-2,2a2=-2a2+2,∴a2=1/2,a=±√2/2
∴原方程得解為:a1=√3,a2=-√3,a3=√2/2,a4=-√2/2